1998
DOI: 10.1172/jci1662
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of antigen-induced inflammatory responses in CD40 ligand knockout mice.

Abstract: The objective of this study was to investigate the contribution of the interaction between CD40 and its ligand (CD40L) to antigen-induced airways inflammatory responses. To this end, we used a model involving ovalbumin (OVA) sensitization followed by OVA aerosol challenge in CD40L knockout (KO) mice. OVA-specific IgE and IgG1 were detected in the serum of the sensitized control, but not in CD40L-KO mice. After antigen challenge, sensitized control mice developed airway inflammation that was primarily eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 43 publications
3
50
2
1
Order By: Relevance
“…BAFF (also known as BlyS, TALL-1, zTNF4, THANK, and TNFSF 13B) has emerged as a critical regulator of B cell survival and maturation in the periphery. Mice deficient in BAFF display severe loss of mature B cells and attenuated antibody responses [8][9][10][11][12][13][14]. The interaction between CD40 and its ligand CD40L is required for T cell-dependent B cell activation and antibody production [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…BAFF (also known as BlyS, TALL-1, zTNF4, THANK, and TNFSF 13B) has emerged as a critical regulator of B cell survival and maturation in the periphery. Mice deficient in BAFF display severe loss of mature B cells and attenuated antibody responses [8][9][10][11][12][13][14]. The interaction between CD40 and its ligand CD40L is required for T cell-dependent B cell activation and antibody production [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from many groups indicate that CD40 probably plays a more general role in immune regulation (6). CD40-CD40 ligand (CD40L) 3 interactions have recently been implicated in airway inflammation (7)(8)(9)(10)(11)(12)(13)(14)(15). Although airway epithelial cells express low levels of CD40, inflammatory cytokines, including IL-1, TNF-␣, and IFN-␥, can all strongly up-regulate the expression of CD40 in airway epithelial cells (16 -18).…”
mentioning
confidence: 99%
“…Using CD40L-null mice that were first sensitized and aerosol-challenged with OVA, studies showed the clear involvement of CD40-CD40L interaction in the development of allergic airway inflammation (10). After Ag challenge, sensitized control mice developed airway inflammation, including production of TNF-␣ and IL-4 and expression of VCAM-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La place du CD154 dans la réaction inflammatoire est soulignée dans les modèles de souris CD154 -/-, chez qui la réponse inflammatoire à un stimulus antigénique est presque abrogée. Le rôle spécifique du CD154 plaquettaire n'a cependant pas été formellement démontré dans ces modèles [29].…”
Section: Réaction Inflammatoireunclassified